Cognitive Duality of the Artistic Concept of Sea-Ocean in B. V. Shergin’s Short Stories - Marina V. Rumyantseva (СибСкрипт, 2024)
Artistic concepts are linguistic and cultural cognitive concepts processed by a particular author. As a result, they acquire the individuality in the text they belong to. In cultural linguistics, artistic concepts help to describe the individual style of an author as a linguistic personality. This article introduces the cognitive features of the binuclear concept of sea-ocean in B. V. Shergin’s short stories. Mythological universals and Russian mythology made it possible to distinguish additional shades of the concept under study, different from its traditional mythological content. The binuclear concept of sea-ocean proved to be a dual artistic concept. Its cores form an equipolar opposition, i.e., they all share the meaning of water space but differ in antonymic values, e.g., life / death, light / darkness, constancy / variability, creation / destruction, etc. These opposite meanings are not mutually exclusive: in fact, they are quite close. The duality is part of the etymology of lexemes ocean and sea: the former has the meaning of living water while the second contains the seme of death, i.e., dead water. In the mythological worldview of the Pomors, who inhabit the White Sea and Russian Arctic coasts, the sea-ocean is the primary matter in which the never-ending struggle of opposites gives birth to the new Universe, which then perishes and is reborn again. This matter is thought of as a living being. The biomorphic features of the concept are expressed through anthropomorphic and zoomorphic codes. The lexical and semantic field man is represented by such lexemes as old father, gray-haired old man, water king, fair judge, soul builder, musician, singer, etc. The lexical and semantic field animal is limited such lexemes as horse and polar bear.